DIPLOMASI INDONESIA DALAM MEMPROMOSIKAN PACU JALUR KUANTAN SINGINGI SEBAGAI DESTINASI PARIWISATA INTERNASIONAL - Aisyah, Siti; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research analyzes Indonesia's diplomacy in promoting the Pacu Jalur festival in Kuantan Singingi as an international tourism destination. The tourism potential of Pacu Jalur in Kuantan Singingi is significant as it has been named one of the top 10 Karisma Event Nusantara (KEN) by the Ministry of Tourism and Creative Economy of the Republic of Indonesia. Pacu Jalur has also been designated by UNESCO as an Intangible Cultural Heritage since 2014 in the category of "Social Practices and Rituals." This study uses a qualitative method with data collection techniques through literature review sourced from books, journals, articles, and websites. The research utilizes the perspective of pluralism and the theory of cultural diplomacy with a state-level analysis. The results of this study conclude that Indonesia has carried out various activities to enhance its soft power in the cultural sector through the development of Pacu Jalur. The diplomacy conducted is based on two soft power instruments: enhancing attraction and strengthening rules (agenda setting) for the development of Pacu Jalur as an internationally recognized tourism destination. Keywords: Pacu Jalur, Cultural Diplomacy, Soft Power